Descriptive Analysis of Islamic Entrepreneurship Characteristics: A Quantitative Study of MSME Actors in South Kalimantan - Rusdina Rusdina; Dina Hermina; Nuril Huda (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
This study aims to analyze and map the level of application of Islamic entrepreneurship (IE) characteristics among Micro, Small, and Medium Enterprises (MSMEs) actors in South Kalimantan. As a pillar of the regional economy, MSMEs in South Kalimantan, which are predominantly Muslim, face the challenge of aligning business practices with Shariah values while also addressing stagnating innovation and local employment dynamics. This research employs a descriptive quantitative approach. Primary data were collected through a questionnaire distributed to 100 Muslim MSME actors in South Kalimantan, selected using purposive and convenience sampling techniques. The research instrument was developed based on five IE dimensions: Shiddiq (Honesty), Amanah (Trustworthiness), Tabligh (Transparency), Fathanah (Competence), and Spirituality. Data were analyzed using descriptive statistics to identify mean scores and levels of implementation. The results show differing profiles of implementation across dimensions. The Spirituality, Shiddiq, and Amanah dimensions exhibit a